CFD studies on the spread of ammonia and hydrogen sulfide pollutants in a public toilet under personalized ventilation. (1st April 2022) - Zhang, Zhonghua; Zeng, Lingjie; Shi, Huixian; Liu, Hua; Yin, Wenjun; Gao, Jun; Wang, Lina; Zhang, Yalei; Zhou, Xuefei
Abstract: The indoor environments of severely polluted toilets are associated with an increased risk of transmission of severe diseases. Enhancing the ventilation effectiveness can improve the indoor air quality (IAQ). The characteristics of pollutant transmission in a public toilet model were analyzed using a computational fluid dynamic program and were further validated based on experimental measurements using a tracer gas (SF6 ). This study investigated the typical pollutant (ammonia and hydrogen sulfide) diffusion characteristics, relationship between the number of air changes per hour and concentration of pollutants, and personal exposure under two types of typical ventilation systems—mixing ventilation (MV) and personalized ventilation (PV)—in public toilets. The results show that MV can reduce the concentration of pollutants in the toilet, but the IAQ cannot reach the desired level. Under a constant total ventilation rate, PV can effectively remove pollutants in the toilet and reduce the concentration of pollutants in the breathing area. The results of this study can contribute to improving the IAQ of public toilets. Highlights: Research on the diffusion of pollutants in toilets using the methods of experimentation and numerical simulation. Choosing the appropriate number of air changes in the mixed ventilation scheme is of great significance for improving the air quality. PV could reduce the ammonia and hydrogen sulfide gases in the human breathing zone to below the national standard value. PV air supply can promote pollutant discharge. When the air supply exceeds 2 h−1 (in this model), it interferes with the discharge of pollutants.